Impact of foreign direct investment on stock prices - Tan, Lay Peng (2015)
Recently, our government has emphasized the needs for Singapore firms to go regional. As a result, many Singapore firms have ventured into China, Vietnam, Malaysia, and others. In this project, our objective is to analyze the impact of the announcement of foreign direct investment on the share price. This report addresses the literature concerning the need for Singapore to build an external economy and the investment vehiches to encourage foreign direct investment. The event study methodology and regression model found that there is positively abnormal returns to be earned based on the announcement of Foreign Direct Investment; that the country of investment makes a difference in the magnitude of the abnormal return on the day of announcement. However, the size of investment and industry do not contribute to the variation of the abnormal returns.